Морфологічні особливості плодів рідкісних видів Iris halophila Pall., I. pumila L., I. hungarica Waldst. et Kit. (Iridaceae Juss.) в умовах інтродукції у лучно-степовому культурфітоценозі - Gritsenko, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2020)
The objective of this study was to analyze the morphological structure and to reveal common and distinguishing features of the fruit in rare steppe species Iris halophila, I. pumila and I. hungarica introduced in conditions of meadow-steppe cultural phytocenosis in the M.M. Gryshko National Botanical Garden, National Academy of Sciences of Ukraine (NBG). Material and methods. Fruits of I. halophila, I. pumila and I. hungarica were collected on the botanical-geographical plot “Steppes of Ukraine” of NBG during 2015–2019. Fruit parameters were measured using a regular ruler. Morphological terms are provided, according to Artyushenko & Fedorov (1986). Colors were determined by Bondartsev’s (1954) scale. Results. In all analyzed species, the fruit is a trimeric and trilocular loculicidal capsule with multi-seeded locules. This capsule is erect, straight, leathery, glabrous, opening by dehiscence from top to bottom along the dorsal veins of carpels. The morphological peculiarities of the fruits, which may be additional diagnostic characters of these species, are established. In particular, in I. halophila capsule is cylindrical, with the upper part elongated into the apical spout (long, thin, bent to the side). The surface of I. halophila capsule is smooth, matte, six-ribbed. Ribs are located on both sides along each of the dorsal veins (i.e., along the dehiscence stria). The dehiscence is complete with diverging upper parts of the valves that remain connected just at the base. The capsule of I. pumila is ellipsoidal, with the upper part also elongated into the apical spout (short, thick, awl-shaped). The surface of I. pumila capsule is wrinkled, without ribs. Commissural (septal) suture and dorsal veins are protruding. The capsule dehisces completely by three slits, but the valves remain connected in the apical part and at the base. The capsule of I. hungarica is oblong-ellipsoidal, without apical spout. The surface is veined, grumous, with six grooves above the commissural sutures and dorsal veins, without ribs. The capsule of I. hungarica opens only partly toward the peduncle, leaving the lower part indehiscent. The upper parts of the valves diverge, while the lower part of the capsule remains unopened. Conclusions. It was found that the shape of the capsule, in particular structure of its upper part, presence of ribs, and apical spout, as well as the surface features together with peculiarities of dehiscence, are constant parameters and can be used as diagnostic characters to distinguish these species. The size and color of the capsules, as well as the number of seeds per capsule of I. halophila, I. pumila and I. hungarica varied, which should be analyzed precisely in future.